Experimental pathogenesis of pullorum disease in chicks by local isolate of Salmonella Pullorum in Bangladesh (Journal of the Bangladesh Agricultural University, 2012)
This study was undertaken to observe the experimental pathogenesis of locally isolated Salmonella enterica subspecies enterica serovar Pullorum in chicks. Fifty chicks were experimentally infected by the oral route with 2 x    107 (CFU) units of Salmonella Pullorum organisms reconstituted in 0.5 ml of sterile phosphate buffer saline (PBS), PH 7.2 and 50 chicks were given only 0.5 ml of sterile PBS as control. Observations were made on clinical signs, gross pathology, and reisolation of S. Pullorum from different organs and blood, histopathological lesions, detection of antibody levels and detection of S. Pullorum by PCR at different time intervals of experimental period. Five birds were randomly selected and sacrificed on 6 hrs before inoculation and 6 hrs, 12 hrs, 24 hrs, 2 days, 3 days, 1st week, 2nd, 3rd and 4th weeks of post infection (PI). The clinical signs of infected chicks were depression, loss of appetite, huddled together, loss of feed and water intake, reduced mean body weights, ruffled feathers, diarrhoea, laboured breathing and pasty vent. The highest gross lesion was (84%) unabsorbed and coagulated yolk and the lowest lesion was (32%) pericarditis and necrotic foci/ nodules in heart. Microscopically, the liver showed congestion, focal necrosis with multifocal infiltration of histiocytes in liver parenchyma. Salmonella organisms were reisolated from different organs and blood at 12 hrs PI. The antibody titre increased gradually and the highest titer was 7275.717 ± 5087.24 at 4 wks PI. In rapid plate agglutination test, the positive result was found from one wk of PI with the sera of infected birds. At 12hrs PI Salmonella was detected by PCR from 20% liver and 20% lung samples of infected birds and no Salmonella was isolated from control group. The orally inoculated Salmonella Pullorum organisms produced lesions in digestive tract, invaded digestive tracts and entered to blood and seeded to different organs in different time intervals and ultimately produced clinical signs, gross and microscopic tissue lesions with immunological response.   DOI: http://dx.doi.org/10.3329/jbau.v10i1.12098   J. Bangladesh Agril. Univ. 10(1): 8794, 2012